Application status and prospect of bovine ovum pick-up and in vitro embryo production technologies - QIU Jinlong; SHI Yan; LI Shuang; ZHANG Kun (浙江大学学报. 农业与生命科学版)
The application of ovum pick-up (OPU) and in vitro embryo production (IVP) can significantly improve the reproductive efficiency of cows, which is of great significance for the propagation of superior breeds of dairy cows and beef cattle. In recent years, OPU/IVP technology has spread rapidly around the world and gradually replaced in vivo derived (IVD) technology to be the most wildly used method of embryo transfer. However, the technical system is still in its infancy in China due to the low efficiency and high technical difficulty in operation, which is the main restriction factor for genetic improvement of dairy cows and beef cattle in China. In this paper, we reviewed the current situation of OPU/IVP, the technical progress as well as the prospect of the application of OPU/IVP in the propagation of superior breeds of dairy cows and beef cattle, aiming to provide references for the complement of China’s OPU/IVP technical system and the improvement of efficiency of bovine reproduction, thereby promoting the development of bovine breeding in China.